EFEKTIVITAS PERAWATAN MANDIRI DIBANDINGKAN KUNJUNGAN RUMAH TERHADAP KEPERCAYAAN DIRI IBU MENYUSUI - Setyawati, Ernani (MEDIA ILMU KESEHATAN, 2018)
Background:Breastfeeding is not always easy. Mother should have high confidence to breastfeed the infant to get positive response in facing difficulties of breastfeeding. Objective: The purpose of this study was to compare the methods of self-care and home visit as the efforts to increase mothers’ brestfeeding self- efficacy. Methods: A comparative analytical study using quasy experimental design including 23 subject selected in the home visit group and 23 subjects in the self-care group by using consecutive sampling technique was taken place in two hospital at Balikpapan, Indonesia. The data were then analyzed by using Wilcoxon and Mann Whitney test. Results: The results showed that mothers’ breastfeeding self-efficacy score before treatment in both groups ( self care =65.52; home visit =63.65) while self-efficacy score after treatment in both groups ( self care =73.39; home visit =74.91). The self-efficacy score in self care groups before and after treatment (ZW = 5.317, p>.05) in home visit groups were Zw=3.564 (p>.05). Mothers’ breastfeeding self-efficacy score in home visit and self care groups before treatment was ZMW = .231 (p>.05). as compared to self-efficacy score in home visit and self care groups after treatment was ZMW = .793 (p>.05). Conclusion: The study showed that home visit method and self-care method are equally good in increasing mothers’ self-efficacy. Keywords: Breastfeeding, home visit, self-efficacy, self care.